Publications CEST - Comité d'éthique en sciences et en technologie (Commission de l'éthique en science et en technologie)

USImap - Unité de santé internationale - Université de Montréal

Responsible innovation in health and health system sustainability: Insights from health innovators’ views and practices - Lehoux, Pascale; Silva, Hudson P; Rocha de Oliveira, Robson; Sabio, Renata P; Malas, Kathy (Health Services Management Research, 2021)
Although healthcare managers make increasingly difficult decisions about health innovations, the way they may interact with innovators to foster health system sustainability remains underexplored. Drawing on the Responsible Innovation in Health (RIH) framework, this paper analyses interviews ( n=37) with Canadian and Brazilian innovators to identify: how they operationalize inclusive design processes; what influences the responsiveness of their innovation to system-level challenges; and how they consider the level and intensity of care required by their innovation. Our qualitative findings indicate that innovators seek to: 1) engage stakeholders at an early ideation stage through context-specific methods combining both formal and informal strategies; 2) address specific system-level benefits but often struggle with the positioning of their solution within the health system; and 3) mitigate staff shortages in specialized care, increase general practitioners’ capacity or patients and informal caregivers’ autonomy. These findings provide empirical insights on how healthcare managers can promote and organize collaborative processes that harness innovation towards more sustainable health systems. By adopting a RIH-oriented managerial role, they can set in place more inclusive design processes, articulate key system-level challenges, and help innovators adjust the level and intensity of care required by their innovation.
Keywords: Libre accès; Publication UdeM

Cadre de référence en transfert de connaissances pour leurs utilisations judicieuses et le soutien à l’innovation - Marie-France, Lafond (2015)
Dans le but d’atteindre une des orientations stratégiques de l’établissement « d’être un établissement de première ligne à vocation universitaire, chef de file en matière de développement et de soutien aux pratiques de qualité et aux pratiques novatrices » 1 , l’établissement s’est doté d’une politique institutionnelle de la recherche, de l’évaluation et du transfert de connaissances 2pour assurer la réalisation d’activités de développement et d’utilisation des connaissances de haut niveau (recherche, évaluation et transfert de connaissances) et ainsi, contribuer à l’amélioration continue de la qualité des soins et des services et à l’innovation en première ligne. Le transfert de connaissances constitue une dimension importante de la mission universitaire de l’établissement. Le CSSS de la Vieille-Capitale a fait du transfert de connaissances un domaine d’expertise à investir. Ce volet de la mission universitaire est en développement au Québec. Afin de poursuivre le développement des connaissances dans ce domaine, l’équipe responsable du transfert s’est étroitement associée aux chercheurs et aux partenaires de l’axe transversal sur le transfert de connaissances au sein du centre de recherche sur les soins et les services de première ligne de l’Université Laval (CERSSPL-UL) ainsi qu’à d’autres chercheurs reconnus dans le domaine au Québec. Les activités de transfert de connaissances sont conçues et structurées de façon à assurer un arrimage étroit entre les milieux de pratique et de gestion de l’établissement et l’équipe de recherche et sa programmation, et ce, en cohérence avec les orientations stratégiques de l’établissement. Le transfert de connaissances concerne un ensemble d’acteurs impliqués dans le développement et l’utilisation des meilleures connaissances pour qu’elles soient mises au service de la population et procurent les retombées attendues au plan de l’amélioration continue de la qualité et de l’innovation. Les chercheurs, le personnel, les gestionnaires, les médecins, les sages-femmes, les stagiaires, les usagers et leurs proches, les bénévoles, les partenaires détiennent des savoirs riches et diversifiés qui font quotidiennement l’objet de transfert de connaissances.
Keywords: Co-production; Innovation; Libre accès; Partenariat; Politiques publiques; Québec; Santé

Articulating care and responsibility in design : A study on the reasoning processes guiding health innovators' 'care-making' practices - Rivard, Lysanne; Lehoux, Pascale; Hagemeister, Nicola (Design Studies, 2021)
This article explores how health innovation designers articulate are and responsibility when designing new health technologies. Towards this end, we draw on Tronto’s ethic of care framework and Responsible Research and Innovation (RRI) scholarship to analyse interviews with Canadian health innovators (n ¼ 31). Our findings clarify how respondents: 1) direct their attention to needs and ways to improve care; 2) mobilise their skill set to take care of problems; 3) engage in what we call ‘care-making’ practices by prioritising key material qualities; and 4) operationalise responsiveness to caregivers and care-receivers through user-centred design. We discuss the inclusion of health innovation designers within the care relationship as ‘caremakers’ as well as the tensions underlying their ways of caring and their conflicting responsibilities.
Keywords: Canada; Publication UdeM; Responsible research and innovation; Réservé UdeM; Éthique

Espaces et lieux d’humanisation : quel statut accorder aux productions techno-scientifiques? - Pelchat, Yolande (Anthropologie et Sociétés, 2003)
La multiplication des innovations techno-scientifiques marque de façon toute particulière le monde contemporain. Quel statut doit-on leur accorder? L’espace actuel de la réflexion critique ne les rend-il pas d’emblée suspectes, sujettes à condamnation, coupables d’une perte de lien social et d’humanité? Axées sur l’efficacité, porteuses d’uniformisation et de contraintes à l’expression du subjectif, ces innovations ne sont-elles pas, par nature, déshumanisantes? Dans cet article, l’auteure tente d’ouvrir d’autres espaces de réflexion pour penser les techno-sciences et la façon dont elles interviennent dans le débat sur la déshumanisation et la réhumanisation. Tirant profit d’une recherche à travers laquelle elle a suivi le travail d’invention d’une nouvelle méthode contraceptive, l’auteure fait valoir la portée, mais aussi les difficultés, d’une démarche qui met en doute les frontières apparemment hermétiques et infranchissables entre ce qui relève du monde des choses et ce qui relève de l’humain.
Keywords: Biotechnologie; Libre accès; Santé; Techno-sciences; technosciences

Comment collaborer avec les municipalités ? Un guide pratique pour les acteurs de la santé publique - Morestin, Florence; publique, Un guide pratique pour les acteurs de la santé; Centre de collaboration nationale sur les politiques publiques et la santé (CCNPPS - Centre de collaboration nationale sur les politiques publiques et la santé, 2020)
Keywords: Libre accès; Municipalités; Partenariat; Québec; Santé publique

Approcher les municipalités pour partager des connaissances : les conseils de fonctionnaires municipaux aux acteurs de la santé publique - Morestin, Florence (Partage de connaissances et politiques publiques, 2019)
En effectuant une revue de littérature sur les différents types de conseillers des décideurs politiques (incluant les fonctionnaires), leur rapport aux connaissances scientifiques et leur rôle dans l’élaboration des politiques publiques (Morestin, 2017), nous n’avons trouvé aucune étude portant sur les fonctionnaires municipaux au Canada. Nous avons donc réalisé des entrevues avec des fonctionnaires de quelques municipalités canadiennes. Dans ce document, nous présentons leur point de vue en réponse à des questions que peuvent se poser les acteurs de la santé publique : - Si je souhaite partager des connaissances avec une municipalité, qui approcher? - Que fait déjà la municipalité dans mon domaine de travail? - Comment établir le premier contact? - Quels types de connaissances les fonctionnaires municipaux jugent-ils utiles? - Comment entretenir de bonnes interactions? - Quel échéancier prévoir? - Officialiser une collaboration avec une municipalité : pourquoi, et sous quelle forme?
Keywords: Libre accès; Municipalités; Politiques publiques; Québec; Santé publique

Assessing and promoting partnership between patients and health-care professionals: Co-construction of the CADICEE tool for patients and their relatives - Pomey, Marie-Pascale; Clavel, Nathalie; Normandin, Louise; Grande, Claudio Del; Ghadiri, Djahanchah Philip; Fernandez-McAuley, Isabel; Boivin, Antoine; Flora, Luigi; Janvier, Annie; Karazivan, Philippe; Pelletier, Jean-François; Fernandez, Nicolas; et al. (Health Expectations, 2021)
Context Partnership between patients and health-care professionals (HCPs) is a concept that needs a valid, practical measure to facilitate its use by patients and HCPs. Objective To co-construct a tool for measuring the degree of partnership between patients and HCPs. Design The CADICEE tool was developed in four steps: (1) generate key dimensions of patient partnership in clinical care; (2) co-construct the tool; (3) assess face and content validity from patients’ and HCPs’ viewpoints; and (4) assess the usability of the tool and explore its measurement performance. Results The CADICEE tool comprises 24 items under 7 dimensions: 1) relationship of Confidence or trust between the patient and the HCPs; 2) patient Autonomy; 3) patient participation in Decisions related to care; 4) shared Information on patient health status or care; 5) patient personal Context; 6) Empathy; and 7) recognition of Expertise. Assessment of the tool's usability and measurement performance showed, in a convenience sample of 246 patients and relatives, high face validity, acceptability and relevance for both patients and HCPs, as well as good construct validity. Conclusions The CADICEE tool is developed in co-construction with patients to evaluate the degree of partnership in care desired by patients in their relationship with HCPs. The tool can be used in various clinical contexts and in different health-care settings. Patient or Public Contribution Patients were involved in determining the importance of constructing this questionnaire. They co-constructed it, pre-tested it and were part of the entire questionnaire development process. Three patients participated in the writing of the article.
Keywords: Co-création; Libre accès; Partenariat; Partenariat avec le patient; Publication UdeM

Documentary research on social innovation in health in Latin America. - Castro-Arroyave, D. M.; Duque-Paz, L. F. (Infectious Diseases of Poverty, 2020)
Background: Identifying social innovation in health initiatives, promoting quality of life through them, and transforming current health conditions demand the knowledge, comprehension and appropriation of the theoretical and methodological developments of this concept. Academic developments in social innovation have mainly occurred in and been documented for English-speaking countries, although...
Keywords: Amérique latine; Innovation sociale; Libre accès; Santé

L’innovation sociale au sein d’une entreprise de la silver economy - Fustec, Benjamin Le (Recherche et Cas en Sciences de Gestion, 2017)
L’entreprise ReSanté-Vous est positionnée sur le secteur de la santé, à destination des personnes âgées. Elle a élaboré une proposition de valeur fondée sur l’innovation sociale. L’étude du cas de ce business model permet de discuter des critères permettant de définir un tel métier, et dans quelle mesure les modèles existants sont bien adaptés à ses dimensions sociales et solidaires, ou de création de valeur sociétale. L’exposé du cas débouche sur l’identification d’une série de forces et faiblesses du modèle économique, et la nécessité de mieux appréhender le concept d’impact social.
Keywords: Entreprise; France; Innovation sociale; Responsabilité sociale; Réservé UdeM; Santé

Des freins à une coopération fructueuse entre professionnels de la recherche et acteurs de la société civile - Vergnas, Olivier Las (Cahiers de laction, 2020)
Cet article s’intéresse aux modes d’interactions entre recherches et société et à la prise en considération de la diversité des productions de connaissances et savoirs. Au lieu d’être fondées sur des relations verticales, où seuls les savoirs reconnus comme scientifiques sont vecteurs de progrès (voir l’article de Marcel Jollivet, p. 61), ces interactions peuvent prendre la forme de recherches participatives construites sur des relations plus horizontales qui font place aux savoirs expérientiels. Dans le premier cas, ces interactions sont des médiations à sens unique alors que, dans le second, il s’agit d’intermédiations au sein de collectifs hybrides réunissant chercheurs et acteurs de la société civile. Les échanges et rapports sociaux au sein de ces collectifs dépendent de « savoirs » radicalement différents, selon que l’on se situe à l’échelle individuelle ou sociétale
Keywords: Innovation inclusive; Réservé UdeM; Santé

Du modèle québécois à l’autoritarisme. La résilience des associations à l’épreuve - Lachapelle, René; Bourque, Denis (Du social business à l’économie solidaire, 2020)
Face à la conception technocratique et entrepreneuriale portée par les pouvoirs publics, une approche alternative de l’innovation sociale, plus populaire et moins visible, à travers l’exploration d’initiatives citoyennes. Prenant comme point de départ le constat d’une appropriation institutionnelle de l’innovation sociale, orientée vers la compétitivité et l’efficacité marchande des expériences de l’économie sociale et solidaire, l’ouvrage vise à la fois à apporter un regard critique sur cette conception de l’innovation sociale et à remettre en lumière des expérimentations citoyennes peu prises en compte par les pouvoirs publics. Il montre ainsi la nécessité d’un tournant épistémologique valorisant les dynamiques de coproduction des savoirs et des politiques entre acteurs, chercheurs et institutions.
Keywords: Associations; Concertation; Gestion axée sur les résultats; Innovation sociale; Philanthropie; Québec; Réservé UdeM; Santé; Éco-développement; Économie sociale; État

Social Innovation For Health Research: Development of the SIFHR Checklist - Kpokiri, Eneyi E.; Chen, Elizabeth; Li, Jingjing; Payne, Sarah; Shrestha, Priyanka; Afsana, Kaosar; Amazigo, Uche; Awor, Phyllis; de Lavison, Jean-Francois; Khan, Saqif; Mier-Alpaño, Jana; Ong, Alberto; et al. (PLOS Medicine, 2021)
Background Social innovations in health are inclusive solutions to address the healthcare delivery gap that meet the needs of end users through a multi-stakeholder, community-engaged process. While social innovations for health have shown promise in closing the healthcare delivery gap, more research is needed to evaluate, scale up, and sustain social innovation. Research checklists can standardize and improve reporting of research findings, promote transparency, and increase replicability of study results and findings. Methods and findings The research checklist was developed through a 3-step community-engaged process, including a global open call for ideas, a scoping review, and a 3-round modified Delphi process. The call for entries solicited checklists and related items and was open between November 27, 2019 and February 1, 2020. In addition to the open call submissions and scoping review findings, a 17-item Social Innovation For Health Research (SIFHR) Checklist was developed based on the Template for Intervention Description and Replication (TIDieR) Checklist. The checklist was then refined during 3 rounds of Delphi surveys conducted between May and June 2020. The resulting checklist will facilitate more complete and transparent reporting, increase end-user engagement, and help assess social innovation projects. A limitation of the open call was requiring internet access, which likely discouraged participation of some subgroups. Conclusions The SIFHR Checklist will strengthen the reporting of social innovation for health research studies. More research is needed on social innovation for health.
Keywords: Innovation inclusive; Innovation sociale; Libre accès; Santé

Food Waste: Addressing our 160 Billion Pound Public Health Challenge with Policy and Business Interventions - Swinburne, Mathew; Sandson, Katie (Journal of Law, Medicine & Ethics, 2019)
The United States wastes approximately 40% of its food supply. This article will examine the implications of this waste for food insecurity and climate change. It will also explore how the law and social entrepreneurship can be used to confront this public health challenge.
Keywords: Réservé UdeM; États-Unis

Supporting Social Innovation in Children: Developing a Game to Promote Health Eating - Ptakauskaite, Nora; Chueng-Nainby, Priscilla; Pain, Helen (Association for Computing Machinery, 2016)
Two things often observed in children: (1) many do not eat a healthy diet and (2) they like playing video-games. Game-based learning has proven to be an effective method for attitude change, and thus has the potential to influence children's eating habits. This study looks at how, through a series of workshop activities, children themselves can inform the design of such games. Using a co-constructive approach, the study's format promotes creativity and control, enabling children to act as valuable informants for its design. Patterns emerging from the study show that children do indeed understand the concept of healthy eating. Future phases of this work will explore whether they understand how various foods affect their bodies. This information will then inform the design of a video-game that encourages healthy eating.
Keywords: Innovation sociale; Réservé UdeM; Santé

Research with a Solidarity Clinic: Design Implications for CSCW Healthcare Service Design - Vlachokyriakos, Vasilis; Crivellaro, Clara; Kouki, Hara; Giovanopoulos, Christos; Olivier, Patrick (Computer Supported Cooperative Work-the Journal of Collaborative Computing and Work Practices)
This paper reports on a long-term collaboration with a self-organised social clinic, within solidarity movements in Greece. The collaboration focused on the co-creation of an oral history group within the social clinic, aiming to record and make sense of a collection of digital oral histories from its volunteers and volunteers-doctors. The process aimed to support reflection and shape the future of the clinic's ongoing social innovation and to transform institutional public health services. Positioning the work of solidarity movement as designing social innovation, the work contributes to CSCW and 'infrastructuring' in Participatory Design aspiring to support social activism and social transformation processes. More specifically, through our empirical insights on the process of infrastructuring an oral history group within a social movement; and related insights about their ongoing participatory health service provision-we provide implications for CSCW concerned with its role in institutional healthcare service transformation.
Keywords: Computer Supported Cooperative Work (CSCW); Europe; Participatory Design; Réservé UdeM

Using Social Innovation as a Theoretical Framework to Guide Future Thinking on Facilitating Collaboration Between Mental Health and Criminal Justice Services - Hean, Sarah; Willumsen, Elisabeth; Ødegård, Atle; Bjørkly, Stål (International Journal of Forensic Mental Health, 2015)
Offender mental health is a major societal challenge. Improved collaboration between mental health and criminal justice services is required to address this challenge. This article explores social innovation as a conceptual framework with which to view these collaborations and develop theoretically informed strategies to optimize interorganizational working. Two key innovation frameworks are applied to the offender mental health field and practice illustrations provided of where new innovations in collaboration, and specifically co-creation between the mental health system and criminal justice system, take place. The article recommends the development of a competency framework for leaders and front line staff in the mental health system and criminal justice systems to raise awareness and skills in the innovation process, especially through co-creation across organizational boundaries.
Keywords: Co-création; Collaboration; Criminologie; Innovation sociale; Justice; Réservé UdeM; Santé

Using the ESID Model To Reduce Intimate Male Violence Against Women - Sullivan, Cris M. (American Journal of Community Psychology, 2003)
This paper describes how the Experimental Social Innovation and Dissemination (ESID) model was successfully used to reduce male violence against women in an intimate relationship. The women in the study who worked with advocates (the key feature of the program) were significantly less likely to be abused again compared to their counterparts in the control condition. They also reported a higher quality of life and fewer difficulties in obtaining community resources even 2 years after the short-term intervention. The advocacy provided consisted of five phases: assessment, implementation, monitoring, secondary implementation, and termination. Assessment collected important information on the client's needs and goals. This involved asking the women what they needed and by observing women's circumstances. In response to each unmet need identified, the advocate worked with the woman to access appropriate community resources. This was the implementation phase. The third phase involved monitoring the effectiveness of the intervention. The advocate and client assessed whether the resource had been obtained and whether it met the identified need. If it was not effective, advocates and clients initiated a secondary implementation to meet the client's needs more effectively. Termination of the intervention consisted of three components. First, advocates emphasized termination dates from the beginning of the intervention in order to prevent termination from surprising the client. Second, beginning about week seven of the 10-week intervention, advocates intensified their efforts to transfer the skills and knowledge the women had acquired throughout the course. Third, advocates left families with written “termination packets,” which contained lists of community resources, helpful tips for obtaining difficult-to-access resources, and useful telephone numbers. A total of 143 women participated in the experimental condition, and women in the control group were not contacted again until their next interview; they received services-as-usual. 30 references
Keywords: Criminologie; Expérimentation; Innovation sociale; Réservé UdeM; Soutien social; États-Unis